Impact of Plant-Based Foods and Nutraceuticals on Toxoplasma gondii Cysts: Nutritional Therapy as a Viable Approach for Managing Chronic Brain Toxoplasmosis - Tan, Sijie; Tong, Wen Han; Vyas, Ajai (Frontiers in Nutrition, 2022)
Toxoplasma gondii is an obligate intracellular parasite that mainly infects warm-blooded animals including humans. T. gondii can encyst and persist chronically in the brain, leading to a broad spectrum of neurological sequelae. Despite the associated health threats, no clinical drug is currently available to eliminate T. gondii cysts. In a continuous effort to uncover novel therapeutic agents for these cysts, the potential of nutritional products has been explored. Herein, we describe findings from in vitro and in vivo studies that support the efficacy of plant-based foods and nutraceuticals against brain cyst burden and cerebral pathologies associated with chronic toxoplasmosis. Finally, we discuss strategies to increase the translatability of preclinical studies and nutritional products to address whether nutritional therapy can be beneficial for coping with chronic T. gondii infections in humans.